Proceeding of the international conference on water problems in the Mediterranean countries, 17-21 November 1997, Lefkoşa, Turkish Republic of Northern Cyprus (Lefkoşa)
2 cilt (1. c. [20], 634 sayfa ; 2. c. [20] sayfa, sayfa 635-1354)